Three phase three layer phase synchronous inverter for microgrid system - Rahman, Towfikur; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A.; Mostafa, Mohammad Golam (2014)
A three phase three layer phase synchronous inverter is used for its high efficiency and simple switching control in the power management system. Compared to conventional inverters its output-waveform has less higher harmonic distortion. The phase synchronous inverter is designed by using well-established theory and used in microgrid power systems. The switching logic control, phase synchronization, low pass filter and DC source coupling for the inverter have been described details in this paper. This study may be useful to the researchers for finding the relevant references especially in the fields of three phase three layer phase synchronous inverter.